2022
DOI: 10.17645/si.v10i2.5092
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences in Gender‐Typical Occupational Orientations Among Adolescents in Germany

Abstract: We illuminate the socio‐cultural embeddedness of adolescents to explain gender‐typical occupational orientations (GTOO) from an intersectional perspective. We investigate whether and why immigrant and native youths differ in their GTOO. These issues are of practical and political importance, as deviations from the norm of the autochthonous majority society can drive change in the gender segregation of the labor market on the one hand but can also lead to difficulties in accessing training and work on the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Yet boys and girls of immigrant origin aspired to somewhat less gender-typical occupations than their majority peers. This finding concurs with a recent study on Germany by Wicht and Siembab ( 2022 ), which showed that students from immigrant backgrounds had less gender-typical occupational aspirations than natives on average, and the difference was especially pronounced for students from Turkey, which is one of the largest immigrant groups in our sample as well. Our findings also indicate that adolescents of immigrant origin orientated themselves toward more integrated occupations, as they were not more likely than their majority peers to aspire to gender-atypical occupations.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Yet boys and girls of immigrant origin aspired to somewhat less gender-typical occupations than their majority peers. This finding concurs with a recent study on Germany by Wicht and Siembab ( 2022 ), which showed that students from immigrant backgrounds had less gender-typical occupational aspirations than natives on average, and the difference was especially pronounced for students from Turkey, which is one of the largest immigrant groups in our sample as well. Our findings also indicate that adolescents of immigrant origin orientated themselves toward more integrated occupations, as they were not more likely than their majority peers to aspire to gender-atypical occupations.…”
Section: Discussionsupporting
confidence: 93%
“…The exploratory nature of this study makes it all the more important to recognize its limitations, as they can highlight possible avenues for future research. Previous studies have shown that immigrant subgroups in the four countries vary markedly in their gender ideologies, educational and occupational aspirations (e.g., de Valk, 2008 ; Wicht and Siembab, 2022 ). It would therefore be insightful to conduct further analyses of specific groups, which were unfortunately beyond the scope of our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Pessl and Steiner (2022) examine the situation of young people with disabilities (YPWD) two years after leaving secondary education, while Patzina et al (2022) investigate first employment. Furthermore, several contributions reflect upon the formation of aspirations and competencies before the transition to upper secondary education, as seen in Wicht and Siembab (2022), Eberhard et al (2022), andKlein et al (2022). The study by Yildiz and Ohnmacht (2022) adds that formative experiences, such as discrimination, occur early in the educational career.…”
Section: The Research Perspectives Of the Thematic Issuementioning
confidence: 99%